2005
DOI: 10.1007/s10681-005-6823-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of RAPD markers linked to the rust (Uromyces fabae) resistance gene in pea (Pisum sativum)

Abstract: Two RAPD markers linked to gene for resistance (assayed as pustule number cm −2 leaf area) to rust [Uromyces fabae (Pers.) de Bary] in pea (Pisum sativum L.) were identified using a mapping population of 31 BC 1 F 1 [HUVP 1 (HUVP 1 × FC 1] plants, FC 1 being the resistant parent. The analysis of genetics of rust resistance was based on the parents, generations. Rust resistance in pea is of non-hypersensitive type; it appeared to be governed by a single partially dominant gene for which symbol Ruf is proposed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 14 publications
1
52
0
Order By: Relevance
“…Many efforts have been made to identify sources of resistance in pea against U. viciae-fabae (Pal et al 1980;Xue & Warkentin 2001;Singh et al 2004;Vijayalakshmi et al 2005;Kushwaha et al 2006). These studies revealed that the majority of the studied pea genotypes were susceptible, though genotypic differences in the rust intensity described as of slow rusting type have been reported (Kumar et al 1994;Chand et al 2006) (Table 1).…”
Section: Screening and Sources Of Resistancementioning
confidence: 99%
See 3 more Smart Citations
“…Many efforts have been made to identify sources of resistance in pea against U. viciae-fabae (Pal et al 1980;Xue & Warkentin 2001;Singh et al 2004;Vijayalakshmi et al 2005;Kushwaha et al 2006). These studies revealed that the majority of the studied pea genotypes were susceptible, though genotypic differences in the rust intensity described as of slow rusting type have been reported (Kumar et al 1994;Chand et al 2006) (Table 1).…”
Section: Screening and Sources Of Resistancementioning
confidence: 99%
“…The dominant nature of partial resistance against faba bean rust U. viciae-fabae in pea, recorded as reduced infection frequency, has been justified as the expression of a single major gene, for which the symbol Ruf was proposed (Vijayalakshmi et al 2005), but the authors also presented some evidence suggesting involvement of some polygenes as well. Further, none of the pea genotypes has been reported to be free from U. viciae-fabae infection (Singh & Sivastava 1985;Chand et al 2006) suggesting a polygenic type of resistance or based on incomplete gene expression.…”
Section: Inheritance Of Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…Several sources of incomplete resistance against U. viciae-fabae have been reported (Pal et al 1980;Xue & Warketin 2001;Vijayalakshmi et al 2005;Chand et al 2006;Kushwaha et al 2006). A single major gene (Ruf) has been reported as responsible for this partial resistance.…”
Section: Rusts (Uromyces Pisi and U Viciae-fabae Pers)mentioning
confidence: 99%